Management skills and labor motivation of business advisors - Custodio Atencio, Kristhel Mariella (2020)
This work has been developed of Mibanco financial institution during 2018, investigating the managerial skills that current bosses possess, as well as the level of work motivation of the business advisors of that institution. With the purpose of determine the relationship between managerial skills and work motivation of Mibanco business advisors in the agency La Victoria-Chiclayo. The design of the present investigation was descriptive correlational, information was obtained from a sample of 32 workers (business advisors), through of the survey technique and instrument the questionnaire. Among the main results, we obtained that more than 60% of business advisors indicate that the managerial skills of their bosses are good and that more than 60% of the same advisors indicate that their work motivation is good. This concludes that, with respect to managerial skills, they have a good level; also, the level of work motivation is good. Finally, the relationship of the variables is proven, where the Pearson correlation coefficient has a value of 0,724; which explains that the relationship between the studied variables is positive of strong level.